Evaluasi Kinerja Guru - Dayu Putri, Halvaziah; Aditia Ainun Putri, Marsha; Julianti, Nofika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Teacher performance evaluation is a crucial aspect of improving educational quality. This study aims to analyze various teacher performance evaluation methods through a literature review. The analysis is based on scientific articles published between 2018 and 2023. The findings indicate that teacher performance evaluation should be conducted systematically, encompassing planning, implementation, and monitoring. This evaluation not only benefits the enhancement of teacher competencies but also contributes to achieving better learning quality. Efforts to improve teacher performance can be carried out through principal supervision, teacher subject discussion programs, training, and the use of application-based technology. Thus, teacher performance evaluation serves as an essential tool to support the success of future education.